Veganismo, antiespecismo e ruptura metabólica: uma geografia das relações contemporâneas entre alimentação e natureza - Lara Palhares Silva Puliero (2024)
The dissertation aims to explore the similarities and proximities between the concept of metabolic rift and food practices related to both meat consumption and the consumption of ultraprocessed vegan foods, understood as part of the hegemonic food system centered on meat. To this end, we explore how this food system interacts with urban space in light of Kohei Saito’s theory of metabolic rift, which examines the disintegration of natural metabolism between society and nature caused by the current mode of production, and in light of Henri Lefebvre’s theory of abstract spaces. On the other hand, we identify practices related to popular/political veganism that seek intersections with social movements, such as the struggle for food sovereignty, to understand whether these could be considered seeds of concrete utopias toward the production of differential spaces, aiming at what we call resgate metabólico. A Rastafari vegetarian food collective was chosen as an empirical object for this analysis. This proposal to connect metabolic rift and space production will allow for advancing the understanding of Geography in these topics, which have so far been little explored in this field of knowledge.